Volume 4: Turbo Expo 2004 2004
DOI: 10.1115/gt2004-53237
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Incidence Angle on the Discharge Coefficient for Rotating Radial Orifices

Abstract: This paper describes an extensive experimental and computational investigation of the fluid flow in radial and radially inclined oriented rotating orifices. Such geometries frequently occur as part of the internal cooling system within gas turbine engines and can also be found in many classes of high speed machinery such as industrial compressors and high speed electrical machinery. The objective of the work was to enhance the understanding of the flows in such geometries and reliably establish discharge coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Considering the similarity of the flow structures of the rotating orifice and the tube entrance, the pressure drop at the tube entrance is analyzed in the way applied in the rotating orifice problem (Idris, Pullen, & Read, 2004). Figure 10 shows the velocity triangle of air at the tube entrance under a rotating coordinate system.…”
Section: The Pressure Drop At the Tube Entrancementioning
confidence: 99%
“…Considering the similarity of the flow structures of the rotating orifice and the tube entrance, the pressure drop at the tube entrance is analyzed in the way applied in the rotating orifice problem (Idris, Pullen, & Read, 2004). Figure 10 shows the velocity triangle of air at the tube entrance under a rotating coordinate system.…”
Section: The Pressure Drop At the Tube Entrancementioning
confidence: 99%
“…However, the effect of rotation was not considered in their study. Idris et al [19,20] confirmed that the discharge coefficient is strongly influenced by the rotation with both numerical and experimental methods. They investigated the effect of the circumferential inclination angle on the discharge coefficient of rotating orifices for the first time.…”
Section: Introductionmentioning
confidence: 94%
“…Comparison of tested orifice geometries with the literature data. 2,4,[6][7][8]10 The core of the rig (Figure 3) consists of four machined aluminium (AlMgSi1) parts, which form the main square section flow channel with dimensions of 20 Â 20 mm 2 . This channel is sealed by round cord.…”
Section: Test Setup Test Rigmentioning
confidence: 99%
“…Idris et al [7][8][9] performed tests and CFD calculations for rotating axial and radial orifices. They assessed orifices with inclinations up to 30 in and against approaching inlet cross-flow.…”
Section: Introductionmentioning
confidence: 99%